Divulgação científica : o uso do infográfico na escola estadual Princesa Isabel - Batista, Daniel Luiz dos Santos (2016)
Scientific Dissemination, a communication strategy to promote the propagation of scientific knowledge, is of paramount importance for the development of science itself, by making information erudite in something simpler and more accessible to all. Nowadays, with a series of alternatives of audiovisual resources, the students turn their attention to more dynamic contents to the detriment of classes that do not present so many mechanisms of attractiveness. Infographics are tools that communication uses to make information more dynamic. Images and texts are used to organize the information in a logical sequence so as to make the subject exposed more attractive and in some cases more simplified. This research seeks to present the potential of the infographic as a tool for Scientific Dissemination being used in science education in public elementary schools. The object of study was the Princesa Isabel State School, in which suggestions of teaching methodology were applied with the use of infographics to dynamize the science class and observe how students of the 4th grade perceive this proposal in the classroom. The results showed that there are concrete possibilities of stimulating the content of science classes with resources of scientific dissemination, especially with the use of infographics. Keywords: Scientific Dissemination, Infographic; Science teaching